Collating LGBTQ+ Friendly Service Providers : Safe Spaces Coalition of the Chippewa Valley Resource Guide - DeLakis, Alex; Kemp, Theresa D. (My University, 2018)
Data from the US Department of Health and Human Services and the Wisconsin Youth Risk Behavior Survey shows that LGBTQ+ people often do not seek services they need due to fear and prior experiences of discriminatory care from service providers. The US Department of Health and Human Services recommends service providers become culturally competent in order to encourage regular care. State and federal government health agencies have called-in communities to engage in reducing stigma, discrimination, and violence faced by LGBTQ+ people. Our Resource Guide links patients and providers in ways that are more equitable.
Color poster with text, graphs and images.
Keywords: LGBTQ+; Customer services; Posters